Pengaruh Konsentrasi Urine Sapi Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Gueneensis Jacq) Pre Nursery Di Polybag - Herlina; Roikan; Khairul Fuad (Fakultas Pertanian, Universitas Warmadewa, 2020)
This study aims to determine the effect of giving the best concentration and concentration of cow urine urine fertilizer on the growth of oil palm seedlings. This research uses a randomized block design (RBD) with 6 treatments U1 = 15 cc / liter U2 water = 30 cc / liter water U3 = 45cc / liter U4 water = 60cc / liter water U5 = 75cc / liter water and U6 = 90cc / liter all concentrated water is given once every 30 days for 3 months varying concentrations and data collection at the age of 90 days. Variables observed were Plant Height, Number of Leaves, Stem Diameter, Normal Seed Percentage. The results showed that the concentration of cow urine liquid fertilizer with different concentrations indicated the highest value at the concentration of U5 = 75 cc / liter of water at plant height.31.94cm Number of strands and 4 strands. Stem diameter of 12.51 mm stems and percentage of normal seedlings .giving a value of 99.48% compared to the concentration of other cow urine urine fertilizers.